Immunological Aspects of Isolation and Confinement - Ponomarev, Sergey; Kalinin, Sergey; Sadova, Anastasiya; Rykova, Marina; Orlova, Kseniya; Crucian, Brian (Frontiers in Immunology, 2021)
Beyond all doubts, the exploration of outer space is a strategically important and priority sector of the national economy, scientific and technological development of every and particular country, and of all human civilization in general. A number of stress factors, including a prolonged confinement in a limited hermetically sealed space, influence the human body in space on board the spaceship and during the orbital flight. All these factors predominantly negatively affect various functional systems of the organism, in particular, the astronaut’s immunity. These ground-based experiments allow to elucidate the effect of confinement in a limited space on both the activation of the immunity and the changes of the immune status in dynamics. Also, due to simulation of one or another emergency situation, such an approach allows the estimation of the influence of an additional psychological stress on the immunity, particularly, in the context of the reserve capacity of the immune system. A sealed chamber seems a convenient site for working out the additional techniques for crew members selection, as well as the countermeasures for negative changes in the astronauts’ immune status. In this review we attempted to collect information describing changes in human immunity during isolation experiments with different conditions including short- and long-term experiments in hermetically closed chambers with artificial environment and during Antarctic winterover.